Botulinum Toxin Type A: A Therapeutic Alternative for Trigeminal Neuralgia – A Literature-Based Overview - Wierzejska, Natalia; Domański, Mikołaj; Kopczyńska, Barbara; Czyżniewska, Oliwia; Czupryńska, Karolina; Otręba, Karina; Szałajska, Julia; Wojcieszek, Maria (Quality in Sport, 2024)
Trigeminal neuralgia (TN) stands as one of the most prevalent forms of craniofacial pain. It commonly targets the areas supplied by the maxillary or mandibular divisions of the trigeminal nerve. Even the slightest stimulation, such as gentle touch can result in severe pain and incapacitation for the patient. The etiology of TN encompasses idiopathic, classic, and secondary classifications. The most common form is the classical type. Carbamazepine and oxcarbazepine are typically the initial pharmacological interventions prescribed for TN, offering relief for many individuals. Considering evidence of varying quality, medications such as lamotrigine, gabapentin, botulinum toxin type A, pregabalin, baclofen, and phenytoin could be viable options, either alone or in combination with carbamazepine or oxcarbazepine, if initial treatments prove ineffective or intolerable. Botulinum toxin type A therapy has shown high efficacy without severe adverse events in alleviating pain in patients with trigeminal neuralgia. This article aims to provide a literature-based overview of trigeminal neuralgia, outlining its unique characteristics, etiology, epidemiology, classification, and management especially using botulinum neurotoxin A.